The Nyayasutra against the Pasupata Conception of God: An Old Interpretation with New Proof - Pajor, Sándor (Religions of South Asia, 2021)
In this paper, I present some possible interpretations of the Nyaya theistic argument, mostly following the analysis of C. Bulcke, highlighting his original interpretation. Other interpretations, which follow the explanations in the Nyayabhasya and the Nyayavarttika, are also presented, as well as an anthropocentric reading introduced by D. H. H. Ingalls, and a sixth possible interpretation suggested by Ferenc Ruzsa. Of course, there are other scholarly accounts of the theistic sutras of the Nyayasutra, but they fall outside the scope of this paper. Before I progress to an analysis of these interpretations, I briefly discuss the development of early Nyaya literature so that we can have a better understanding of this system and the legitimacy of numerous interpretations of the very same sutras.